Effect of the introduction of a lumbar-puncture sticker and teaching manikin on junior staff documentation and performance of paediatric lumbar punctures. Issue 5 (30th October 2006) - Taitz, J; Wyeth, B; Lennon, R; Torre, P D; Yen, T; Harrison, B; Cattell, M
Abstract : Background: Performing a lumbar puncture in an unwell child can cause anxiety in both the parent and the junior doctor. There is increasing evidence of post-lumbar-puncture complications in this age group. Aims: To improve the documentation, consent for and technical performance of paediatric lumbar punctures to 100% of the required standard within 3 months. Setting: The paediatric emergency department of a the Royal North Shore Hospital (University of Sydney, Sydney, Australia). Participants: Paediatric emergency staff, including residents, registrars and consultants. Methods: Medical records of 40 consecutive children who had undergone a lumbar puncture in the 6 months before the introduction of the lumbar-puncture proforma were reviewed. After introduction of the proforma, the records of 25 consecutive patients were reviewed to assess changes in the outcome measures. Before introduction of the proforma, junior medical staff were instructed in the procedure using specialised lumbar puncture manikins (Baby Stap; Laerdel, USA). Results: Before introduction of the proforma, the median number of documented indicators was 4, out of a maximum of 12. There was almost no documentation of parental consent, patient complications and analgesia. Introduction of the proforma resulted in a highly marked increase to a median of 12 documented indicators per patient (p<0.01, 95% confidence interval 6 to 8). Conclusions: The introduction of a lumbar-puncture proforma and formal teaching sessions using a paediatric manikin led to a marked improvement in the documentation of paediatric lumbar-punctures. Lumbar-punctures can be performed only by accredited medical officers who have achieved competency on the lumbar-puncture teaching manikin.